Statistical methods. - Stefan Szulc; H. Infeld and C. D. I. Forrester, of "Metody statystyczne", Warsaw, 1961. (Oxford : Pergamon Press, 1961)
This book is concerned with certain facts, the knowledge of which helps in understanding modern statistics.
aia 26/09/17
Loans
Keywords: Statistics